Letter - Le Gros Clark, F.
C02-0066-001 COMMITTEE AGAINST MALNUTRITION HON SECRETARY - F LE GROS CLARK 19c EAGLE STREET LONDON W C 1 CHANCERY 7567 HON TREASURER - Mrs ANNE McNALLY 17 CHARLOTTE ST LONDON W 1 - MUSEUM 0994 19/5/38. Dear Dr Morgan, I have slept on and meditated on last night's meeting. As a result I have come to the conclusion that, in obedience to a purely rational motive, I was a little unguarded. I beg you to forgive me if this seemed to be so. I usually try to sum up tendencies in a meeting and only to speak when I feel that I have a reasonable contribution to make. It was the fact that there seemed to me to be a difficulty about the lawyers that made me consider the idea of representation from the Haldane Club one that would resolve the apparent difficulty. When what seemed to me be reasonable met with opposition, I was for the time astonished. But, believe me, I have no intention of protecting what seemed a reasonable point, when there may be factors of which I am unaware. As to the lawyer representation, I have no wit of objection to your choices personally. Why should I? I hope the ruffling atmosphere will be settled again as before. Believe me - Yours sincerely, F. le Gros Clark 292C/946/2/66